Large Demographic Shocks and Small Changes in the Marriage Market. Issue 6 (2nd August 2016) - Brandt, Loren; Siow, Aloysius; Vogel, Carl
Abstract: Between 1958 and 1961, China experienced a drastic famine. The famine substantially reduced birth rates and also adversely affected the health of these famine-born cohorts. This paper provides nonparametric estimates of the total effects of the famine on the marital behavior of famine-affected cohorts in rural Sichuan and Anhui. These reduced-form estimates incorporate general equilibrium and heterogeneous treatment effects. The paper uses the Choo–Siow model to decompose observed marital outcomes into quantity and quality effects. A decline in marital attractiveness of famine-affected cohorts, which is correlated with an increase in marital childlessness, provides support for the external validity of the Choo–Siow decomposition. The small observed changes in marriage rates of the famine-born cohorts are due to a substantial decline in their marital attractiveness.